الرقابة القضائية على العملية الانتخابية على ضوء القانون العضوي رقم 16/10 المتعلق بنظام الانتخابات - مصطفى، خليف (جامعة زيان عاشور بالجلفة, 2017)
أصبحت الرقابة القضائية على العملية الانتخابية من أهم المواضيع إثارة للجدل، سواء على المستوى المحلي أو الخارجي، خاصة مع تصاعد الانتخابات الموجهة لهذه العملية بغرض الطعن في نزاهتها، فتم اللجوء إلى السلطة القضائية باعتبارها صاحبة الاختصاص الأصيل بالفصل في مختلف النزاعات التي تنشأ بين الأفراد والإدارة، وخاصة ما تعلق منها بالمنازعات الانتخابية، من خلال سلطة الفصل في مختلف الطعون الانتخابية والنظر في التجاوزات التي تشكل في نظر القانون جرائم تمس بنزاهة العملية الانتخابية، وهو ما يعمل المشرع الجزائري على تكريسه في مختلف القوانين الانتخابية التي عرفتها المنظومة التشريعية الانتخابية الجزائية، حيث منح السلطة القضائية سلطات وآليات قانونية تمكنها من التدخل في الوقت المناسب للفصل في مختلف الإشكالات التي تعترض العملية الانتخابية، دون المساس بالصلاحيات المخولة للأجهزة الرقابية الأخرى، كالمجلس الدستوري، والهيئة العليا المستقلة لمراقبة العملية الانتخابية.
The juridical oversight on the election process becomes the most important controversial object upon twice the local and the external fields, even with the increase of the critical speeches towards this operation aimed to thrust its eligibility, but whose part can guarantee that. They have recourse to the juridical authority, sight its competence to adjudge in different lawsuits between the administration and persons, especially the election recourses, by adjudging the different recourses and to examine the different transgressions which from crimes in view of law. This is what the Algerian legislator tries to establish it en different election laws, whose had given the juridical authority to the juridical instances which allow it to interpose in just time to adjudge the different problematic which disturb the election operations, without disturbing the function of the oversight instances, such as the constitutional council, and the high independent instance to oversight the election operations.
Keywords: القوانين والتشريعات -- الرقابة القضائية -- العملية الانتخابية -- القانون العضوي -- قانون الانتخابات -- السلطة القضائية -- الجزائر